2016
DOI: 10.1002/mde.2791
|View full text |Cite
|
Sign up to set email alerts
|

Pro Sports League Antitrust ‘Beliefs’: Applied Theory and the Rule of Reason

Abstract: In antitrust rule of reason cases, courts weigh anticompetitive harm against consumer welfare offsets. In sports cases, the courts appear to accept claims that fans prefer more competitive balance to less, so that a potential welfare offset is any added enhanced competitive balance attributable to the anticompetitive activity. In addition, courts often decide that less intrusive alternatives may be available to accomplish the same competitive balance gain. From the applied theory perspective, this is troubleso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Sung and Mills (2018) found a U-shaped relationship between stadium attendance and the home team's winning probability, providing evidence contradictory to the UOH. As such, there is still a need for substantial examination of fan preferences for outcome uncertainty in various professional sports contexts, as Fort (2017) noted. However, recent empirical studies on European soccer leagues have revealed that fans are loss-averse and prefer games with more certain outcomes (Cox, 2018, on the EPL; Martins & Cró, 2018, on the Portuguese Primeira Liga; Besters et al, 2019, on the Dutch Eredivisie).…”
Section: Contextual and Theoretical Backgroundmentioning
confidence: 99%
“…Sung and Mills (2018) found a U-shaped relationship between stadium attendance and the home team's winning probability, providing evidence contradictory to the UOH. As such, there is still a need for substantial examination of fan preferences for outcome uncertainty in various professional sports contexts, as Fort (2017) noted. However, recent empirical studies on European soccer leagues have revealed that fans are loss-averse and prefer games with more certain outcomes (Cox, 2018, on the EPL; Martins & Cró, 2018, on the Portuguese Primeira Liga; Besters et al, 2019, on the Dutch Eredivisie).…”
Section: Contextual and Theoretical Backgroundmentioning
confidence: 99%
“…Overall, uncertainty of outcome hypothesis is a form of speculation of fan preferences, which are assumed to be inherently different from individual to individual. Thus, further investigation is needed to reveal fan preferences in various contexts, as Fort (2017) noted.…”
Section: Determinants Of Viewership For Sportmentioning
confidence: 99%
“…These leagues argue that domination by a single champion would result in a loss of fan interest, or more generally that an unequal distribution of competitiveness across teams may eventually hurt aggregate profits due to waning fan interest (Neale, 1964;Rottenberg, 1956). Leagues therefore claim to promote CB leading to outcome uncertainty (OU)as a fundamental characteristic of their economic success, which has long been used as a central defense for favorable antitrust treatment in North America (Fort, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Given this mixed evidence, and as noted by Fort (2017), individual leagueswhich vary in their structure, fan base, and labor supplyrequire careful examination and consideration for consequences of league CB and OU. For example, Major League Soccer (MLS) adopted a relatively unique single-entity structure upon its founding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation